50 Macroscopic and microscopic analysis of the left atrial appendage with a view to a novel ablation strategy for atrial fibrillation. (5th October 2017) - Hensey, M; O'Neill, L; Mahon, C; Fabre, A; Keane, D
Abstract : Introduction: The left atrial appendage (LAA) has a key role in the formation of thrombus and subsequent embolic complications in atrial fibrillation (AF). It has been studied extensively, from recent interest in the various morphologies of the LAA and relative risk of thrombus to LAA occlusion and LAA ablation. Methods/Results: Eleven post-mortem LAA samples were collected for visual analysis, two were not included due to poor sample quality. On examination of the nine remaining samples, several common patterns of pectinate muscle orientation were noted. The LAA samples were noted to have a smooth circumferential neck of muscular tissue giving rise to a dominant singular smooth trunk of papillary muscle in 7 cases and two trunks in 2 cases. These trunks were either shallow (5 samples) or more muscular and raised (4 samples) (Figure 1). Shallow trunks tended to be wider than the raised trunks and may even be circumferential (2 samples). The main trunk arborised to give off papillary muscle branches down to third or fourth order branches. The samples were visually assessed for the percentage of smooth papillary muscle versus non-papillary recesses and were found to have 50% smooth muscle in 3 samples, 50–75% in 3 samples and >75% in 3 samples. We performed histological analysis of further LAA samples collected during cardiac surgery in a parallel study. We identified a distint pattern of myocyte orientation from the neck, mid-section and apical section of the LAA. The neck of the LAA had dense circumferential orientation of the myocytes. In the mid-section, arborisation of the papillary muscles can be appreciated with fibrous separation between myocyte bundles. Finally, in the apical segment of the LAA, myocytes can be seen reaching the epithelial surface in discrete bundles with very little communication between each bundle, often limited to one or two individual myocytes (Figure 2). Conclusions/Implications: We have identified via the examination of a small number of LAA's a common pattern of macroscopic papillary muscle orientation. Histological analysis of further samples has shown arborisation of myocyte fibres with minimal communication in distal segments of the LAA. We hypothesize that this information could be used to include a specific LAA ablation strategy for persistent AF. If the ostium of the LAA was ablated in a near-circumferential pattern leaving only a small gap in line with the predominant myocardial trunk that this could organize LAA activity with potential amelioration of its roles in the maintenance of persistent AF and in thrombostasis.